The Influence of Foreign Ownership on Corporate Social Responsibility (CSR) Companies Based on Law Number 25 of 2007 on Investment - Probosambodo, Yokhebed Arumdika; Laksito, FX. Hastowo Broto (Indonesian Journal Publisher, 2025)
This research was conducted with the aim of exploring the influence of foreign ownership on Corporate Social Responsibility (CSR) practices, to what extent the impact is positive or negative. This research uses descriptive analysis methods with a quantitative approach. The research results show that foreign ownership plays an important role in encouraging companies to adopt stricter CSR practices that align with international standards. This research reveals that foreign ownership plays a crucial role in encouraging companies to adopt stricter CSR practices that align with international standards. Companies with foreign ownership are more likely to allocate greater resources to CSR initiatives and collaborate with external stakeholders. The laws of the Republic of Indonesia, particularly the Investment Law, provide an important legal basis to encourage Corporate Social Responsibility (CSR), but its effectiveness depends on various factors, including law enforcement, oversight, and the awareness of all parties. It is important for companies with foreign ownership.